Botulinum toxin blocks mast cells and prevents rosacea like inflammation. Issue 1 (January 2019) - Choi, Jae Eun; Werbel, Tyler; Wang, Zhenping; Wu, Chia Chi; Yaksh, Tony L.; Di Nardo, Anna
Abstract: Background: Rosacea is a chronic inflammatory skin condition whose etiology has been linked to mast cells and the antimicrobial peptide cathelicidin LL-37. Individuals with refractory disease have demonstrated clinical benefit with periodic injections of onabotulinum toxin, but the mechanism of action is unknown. Objectives: To investigate the molecular mechanism by which botulinum toxin improves rosacea lesions. Methods: Primary human and murine mast cells were pretreated with onabotulinum toxin A or B or control. Mast cell degranulation was evaluated by β-hexosaminidase activity. Expression of botulinum toxin receptor Sv2 was measured by qPCR. The presence of SNAP-25 and VAMP2 was established by immunofluorescence. In vivo rosacea model was established by intradermally injecting LL-37 with or without onabotulinum toxin A pretreatment. Mast cell degranulation was assessed in vivo by histologic counts. Rosacea biomarkers were analyzed by qPCR of mouse skin sections. Results: Onabotulinum toxin A and B inhibited compound 48/80-induced degranulation of both human and murine mast cells. Expression of Sv2 was established in mouse mast cells. Onabotulinum toxin A and B increased cleaved SNAP-25 and decreased VAMP2 staining in mast cells respectively. In mice, injection of onabotulinum toxin A significantly reduced LL-37-induced skin erythema, mast cell degranulation, and mRNA expression of rosacea biomarkers. Conclusions: These findings suggest that onabotulinum toxin reduces rosacea-associated skin inflammation by directly inhibiting mast cell degranulation. Periodic applications of onabotulinum toxin may be an effective therapy for refractory rosacea and deserves further study.